2011
DOI: 10.1177/197140091102400223
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Corpus Callosum Abnormalities Associated with Antiepileptic Drugs in Temporal Lobe Epilepsy

Abstract: Epilepsy is more than a grey-matter disorder affecting large white matter connections of the brain with seizure generation and propagation. The mechanism for such changes remains unclear. The purpose of this study was to investigate the microstructural changes in the corpus callosum in temporal lobe epilepsy (TLE) patients and whether these abnormalities are related to antiepileptic drug (AED) therapy. Ten TLE patients receiving AED therapy, ten TLE patients with no therapy and ten controls were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This allowed us to evaluate the relation of the dose‐reduction rates of all anticonvulsants and to correlate them with the presence of FESCC. Furthermore, we investigated relative diffusion restriction in the splenium corporis callosi as a quantitative, objective measure of focal edema, which to our knowledge has not been done in the context of FESCC . This analysis lent further support to the role of sodium channel blocker dose‐change rates in the pathophysiology of FESCC.…”
Section: Discussionmentioning
confidence: 97%
“…This allowed us to evaluate the relation of the dose‐reduction rates of all anticonvulsants and to correlate them with the presence of FESCC. Furthermore, we investigated relative diffusion restriction in the splenium corporis callosi as a quantitative, objective measure of focal edema, which to our knowledge has not been done in the context of FESCC . This analysis lent further support to the role of sodium channel blocker dose‐change rates in the pathophysiology of FESCC.…”
Section: Discussionmentioning
confidence: 97%
“…Fibre atrophy in the splenium of the corpus callosum, apparent from the reduction of all three observed parameters, is more probably the result of the drug treatment and seizures. DTI-based studies have shown that WM bundles of the splenium of the corpus callosum are more prone to structural abnormalities as a consequence of antiepileptic drug usage and they are also associated with seizure frequency, resulting in secondary WM degeneration 53,[60][61][62][63] . Moreover, callosal fibres, cingulum bundles, inferior longitudinal fasciculus, arcuate fasciculus, and uncinate fasciculus have been reported to be associated with different seizure propagation directions (antero-posterior and medio-lateral spread), suggesting that a decrease in fibre microstructure parameters in these tracts is driven by seizure propagation rather than being a cause of seizures 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, use of antiepileptic drugs (Gunbey et al, 2011) and heterogeneity in TLE etiology (Scanlon et al, 2013) have also been shown to affect DTI. Earlier age of onset has also been associated with decreased hippocampal volumes (Trenerry et al, 1993).…”
Section: Discussionmentioning
confidence: 99%